2021
DOI: 10.1016/j.pathol.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic features of Annexin A2 expression in prostate cancer

Abstract: ANXA2 (Annexin A2 or Annexin II) is a calcium dependent phospholipid binding protein with diverse cellular functions. While ANXA2 is either absent or expressed focally in the prostate epithelium of well and moderately differentiated tumours, it is highly expressed in a subset of poorly differentiated tumours. Here we examined the association between ANXA2 expression and tumour progression, with consideration of ERG expression status and patient race (Caucasian American and African American). We evaluated ANXA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Inhibition of these interactions by synthetic peptides, immunotherapeutic agents, siRNA or aptamers abolish membrane localization and restrict cancer progression [30] , [31] , [32] , [33] , [34] , [35] . Elevated levels of AnxA2 in tumors correlate with drug resistance and poor prognosis in multiple metastatic tumors including renal, pancreatic, liver, urothelial, and lung cancers [36] , [37] , [38] , [39] ( https://www.proteinatlas.org/ENSG00000182718-ANXA2/pathology ). As a secretory protein, circulatory AnxA2 levels are reported to be elevated in metastatic hepatocellular and breast cancers [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of these interactions by synthetic peptides, immunotherapeutic agents, siRNA or aptamers abolish membrane localization and restrict cancer progression [30] , [31] , [32] , [33] , [34] , [35] . Elevated levels of AnxA2 in tumors correlate with drug resistance and poor prognosis in multiple metastatic tumors including renal, pancreatic, liver, urothelial, and lung cancers [36] , [37] , [38] , [39] ( https://www.proteinatlas.org/ENSG00000182718-ANXA2/pathology ). As a secretory protein, circulatory AnxA2 levels are reported to be elevated in metastatic hepatocellular and breast cancers [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Third, the current analysis obtained hub genes and module lncRNAs with significant differential expression (CCR1, CCL3, CCL4, PACSIN1, CGNL1, TRIM69, STAB2, ATP8A1, CD48, NOL6, ZFP36, KLF4, CD247, REEP6, SQRDL, KCNJ6, ANXA2, SPRY2, KCNS3, ITM2C, THBS2, CTD-2515H24.2, LL21NC02-21A1.1, LOC200772, RP11-402C9.1, LINC01203, RP11-479G22.8, RP11-615I2.1, RP1-249I4.2, RP11-116N8.2 and RP11-288L9.4). As an example, ANXA2 is a pleiotropic calcium-dependent phospholipid-binding protein that is abnormally expressed in a variety of cancer types ( 59 ), including prostate cancer ( 60 ) and liver cancer ( 61 ). Liu et al ( 62 ) performed a meta-analysis and indicated that ANXA2-overexpression might be related to poor outcomes in patients with malignant tumors, which is consistent with the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Within the process of STAT3 activation, Anxa2 with a phosphor-Tyr23 is identified as a novel dominant regulator for STAT3-Tyr705 phosphorylation, which is responsible for nuclear entry and transcriptional activation of STAT3 (Figure 1A-C). As Anxa2 expression and phosphor-Tyr23 are largely evaluated in various cancer types [16][17][18][19][20][21]34], this regulatory mechanism towards STAT3 somehow outstands as an assignable target for STAT3 inhibition. Anxa2 has been proven facilitating cancer progression via multiple aspects by interacting with other biomolecules, among which the Anxa2 rearrangement gene expression in cancer cells through oncogenic transcription factor like NF-κB, YAP1 in Hippo pathway and STAT3/6 [22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Annexin A2 (Anxa2) is well-described as the heavy chain of Anxa2-S100A10 (A t) complex for plasmin processing [14,15]. Recent researches on cancers indicate that Anxa2 is over-expressed in various types of cancers, promotes cancer development, metastasis and chemo-resistance, highly associated with poor prognosis [16][17][18][19][20][21]. Detailed mechanisms are revealed that Anxa2 interacts with transcriptional factors and enhances their activation including NF-κB, STAT3/6 and YAP1 [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%